2016
DOI: 10.1063/1.4944620
|View full text |Cite
|
Sign up to set email alerts
|

Long range stress correlations in the inherent structures of liquids at rest

Abstract: Simulation studies of the atomic shear stress in the local potential energy minima (inherent structures) are reported for binary liquid mixtures in 2D and 3D. These inherent structure stresses are fundamental to slow stress relaxation and high viscosity in supercooled liquids.We find that the atomic shear stress in the inherent structures (IS) of both liquids at rest exhibits slowly decaying anisotropic correlations. We show that the stress correlations contributes significantly to the variance of the total sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…In our view, it is worth making here a comment related to the history of application of the Green-Kubo expression. As far as we understand, the original derivations of the Green-Kubo expression [42][43][44] are actually microscopic and thus microscopic considerations adopted relatively recently [11,14,15,[22][23][24][33][34][35][36][37][38][39][40][41] are much closer in spirit to the derivations of the Green-Kubo expression than the macroscopic view of the Green-Kubo expression usually used. Our research of the literature suggests that the macroscopic view of the microscopically-derived Green-Kubo expression has been adopted in one of the first papers on viscosity calculations in computer simulations [70] (see also Ref.…”
Section: The Green-kubo Expression For Viscosity and Microscopic mentioning
confidence: 99%
See 1 more Smart Citation
“…In our view, it is worth making here a comment related to the history of application of the Green-Kubo expression. As far as we understand, the original derivations of the Green-Kubo expression [42][43][44] are actually microscopic and thus microscopic considerations adopted relatively recently [11,14,15,[22][23][24][33][34][35][36][37][38][39][40][41] are much closer in spirit to the derivations of the Green-Kubo expression than the macroscopic view of the Green-Kubo expression usually used. Our research of the literature suggests that the macroscopic view of the microscopically-derived Green-Kubo expression has been adopted in one of the first papers on viscosity calculations in computer simulations [70] (see also Ref.…”
Section: The Green-kubo Expression For Viscosity and Microscopic mentioning
confidence: 99%
“…ally considered since ρ p (r) has the clear physical meaning while G p (r) can be obtained by Fourier transform from the experimental scattering intensity [1]. We, however, consider here the CFs with the additional r factor because these functions allow making more direct comparisons with the stress CFs (3,4,5,6,10,11,12,13) which are directly relevant to viscosity. Note again that CFs (7,14) contain in themselves the correlation of a chosen particle (bond) with all other particles (bonds) at some distance from it, i.e., they also include in themselves the factor 4πr 2 .…”
Section: A the Average Correlation Functionsmentioning
confidence: 99%
“…Insights into this can be gained for the present LJ system by considering a spatially resolved shear stress correlation function, [72][73][74] …”
Section: Microstructural Origins Of Shear Thinning In Nemd and Thementioning
confidence: 99%
“…In several recent publications it has been discussed that the inherent structures of the model liquids have non-zero macroscopic stress states [4][5][6]. It has been demonstrated that these non-zero stress states are related to the boundary conditions which put constraints on the allowable configurational states of the systems [5].…”
Section: Introductionmentioning
confidence: 99%
“…Over the several decades the mechanism of the stress relaxation in supercooled liquids has been extensively discussed [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Many of these considerations address stress relaxation through considerations of the stress correlations relevant to the Green-Kubo expression for viscosity [3][4][5][6][7][8][9][10][11][12][13][14]19]. In particular, it has been shown that in deeply supercooled liquids (parent liquids) relaxation of the Green-Kubo stress correlation function at large times corresponds to the relaxation of the Green-Kubo stress correlation function calculated on the inherent structures (i.e., on the structures obtained through "an instant quench" from the parent liquid structures) [4][5][6]19].…”
Section: Introductionmentioning
confidence: 99%